Three Pseudocerotidae species (Platyhelminthes, Polycladida, Cotylea) from the Argentinean coast - Bulnes, Verónica N.; Albano, Mariano J.; Obenat, Sandra M.; Cazzaniga, Néstor J. (Zootaxa, 2011)
Three species of flatworms, Phrikoceros mopsus (Marcus, 1952), Thysanozoon brocchii (Risso, 1818) and Thysanozoon mirtae sp. nov., are described from specimens collected from shallow rocky shores of Mar del Plata harbour, in the southwestern Atlantic. P. mopsus had been described as living in the coasts of Brazil and southern Patagonia. T. brocchii has a more extensive known distribution, from the Mediterranean to the coasts of Brazil and the Argentinean Patagonia. Their morphological variation is here recorded and discussed. Thysanozoon mirtae sp. nov. is characterized by its colour pattern, colourless tentacles, and the presence of well developed spermiducal vesicles and a strong parenchymatic musculature.